Influence of Application of Work Safety System to Employee Performance - Harsono, Yhonanda; Ratnawati , Elfrida; Qurtubi, Ahmad; Natalia Hia, Liberti; Hasanah, Alfiyah (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the application of work safety systems and employee performance on Ciputat Skyrope. The research method in this research is descriptive quantitative and uses primary and secondary data types, and using a questionnaire instrument, the number of this study was 87 respondents using the sampling research method used is saturated sampling. The method of data analysis uses statistical formulas, namely validity, reliability, product moment correlation test, simple linear regression test, determination test, and hypothesis significance test. Based on the results of the study, a correlation coefficient of 0.6344 was obtained, which means there is a strong influence between the variables X and Y. With the linear regression equation in the study, Y = 16.63 + 0.6079, meaning that if the value of X (implementation of the work safety system) increases by one unit, the value of Y (employee performance) will rise, and vice versa. While the coefficient of determination obtained a value of 40.24%. This shows that the effect of the implementation of the Safety System on Employee Performance is 37.04%, and the remaining 59.76% is influenced by other factors. The value of t_count obtained is 7.565; this is greater than t_table (1.988), then H_0 is rejected and Ha is accepted, meaning that there is a significant effect between the implementation of work safety systems on employee performance.